Are SNIP’s still desirable in sports genomics? - Sližik, Miroslav; Pospieszna, Barbara; Gronek, Joanna; Sworek, Robert (Akademia Wychowania Fizycznego w Poznaniu)
A single-nucleotide polymorphism (SNIP) is a variation in a single nucleotide that occurs at a certain position in the DNA. Each variant is, to some extent, present within a population (e.g. > 1%). Due to the correlations of some SNIP’s with sport performance and athletic physical capacity, various authors considered their importance in the context of professional sport. Among many SNIP’s angiotensin I converting enzyme (ACE) polymorphism is a well-studied example associated with an enhanced physiological response to aerobic exercise. Among other sport-related interesting SNIP’s following are highly documented: AMPD1 (C34T) Gln12 Allele, BDKRB2 rs5810761, UCP’s and eNOS rs1799983
Keywords: nucleotide polymorphism; sport performance; genetic predisposition